2005
DOI: 10.3748/wjg.v11.i19.2953
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography findings in fatal cases of enormous hepatic portal venous gas

Abstract: HPVG is a diagnostic clue in patients with acute abdominal conditions, and CT is the most specific diagnostic tool for its evaluation. The dry mesenteric veins are the suggestive fatal sign, especially for the deteriorating patients, with the direct effect on gastrointestinal perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 8 publications
0
45
0
1
Order By: Relevance
“…Most human patients suffer from concurrent underlying diseases which predispose them to the development of HPVG, including chronic renal disease, hypertension, immunosuppression, diabetes mellitus, recent gastrointestinal surgery, alcoholism, and ischaemic heart disease (Chan et al . 2005). Iatrogenic causes include blunt abdominal trauma (Stuijvenberg et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most human patients suffer from concurrent underlying diseases which predispose them to the development of HPVG, including chronic renal disease, hypertension, immunosuppression, diabetes mellitus, recent gastrointestinal surgery, alcoholism, and ischaemic heart disease (Chan et al . 2005). Iatrogenic causes include blunt abdominal trauma (Stuijvenberg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Even though uncommon, it should be considered in people presenting to the emergency room with signs of acute abdomen as this condition has historically carried a high mortality rate in humans (Chan et al . 2005). The first published case in an adult patient was identified in 1960 (Susman & Senturia 1960), in a patient who suffered from gas embolization of the portal venous system.…”
Section: Introductionmentioning
confidence: 99%
“…1) or within the intrahepatic portal vein. 2,4,14,15 In our review, we identified patients with PI or PVG or both, and feel that they likely represent different phases of the same pathophysiology. This paper addresses PI of any portion of the GI tract and PVG with the expectation that we can better describe the clinical spectrum of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used diagnostic modality is a CT scan, which is extremely sensitive [14,15]. Endoscopy can be used to confirm air in the lamina propria of the tissue, as well as to rule out the non-gangrenous causes of pneumatosis.…”
Section: Discussionmentioning
confidence: 99%